Pacto nacional pela alfabetização na idade certa: repercussões de uma política curricular nas práticas de alfabetização na rede pública de ensino no Rio Grande do Sul - Silva, Cármen Maria França da (2019)
This Master's dissertation is part of the research line Policies and Management of Basic and Higher Education of the Graduate Program, Professional Master in Public Policy and Educational Management of the Federal University of Santa Maria (UFSM). It presents as themes the curriculum policy, literacy and continuing education of literacy teachers. A preliminary analysis of works published from 2013 to 2018 focusing on this theme showed the existence of a significant number of publications on the National Pact for the Right Age Literacy Program - PNAIC and literacy practices. Given this, this dissertation aims to investigate the repercussion of the PNAIC curriculum policy on literacy practices of teachers of the literacy cycle in public schools in RS. The methodology used is based on the quantitative and qualitative approach, using the theoretical and methodological assumptions case study. Information was collected from an online questionnaire using the SurveyMonkey tool, sent to literacy teachers from the first three years of elementary school who are registered in the Integrated Monitoring and Execution System - SIMEC. The discussions were based on legislation, official documents from the Ministry of Education, PNAIC Notebooks and authors such as: Ferreiro and Teberosky (1999), Ferreiro (2013), Soares (2013, 2016), Pacheco (2003), Sacristan (2013), Antunes (2011), Leo (2011), Tardif (2014), among others. The analysis was performed based on the recurrence of thematic units that indicated the analysis categories: Being a literacy teacher in the public school of Rio Grande do Sul; Continuing Training of Literacy Teachers; Curriculum textures and literacy practices. Thus, it was possible to recognize the trajectory of the literacy teachers, the paths taken for the construction and reframing of their knowledge about literacy practices, identifying the profile of this professional. Thus, it was understood that continuing education needs to be organized in order to promote formative experiences aimed at transcending the challenges of professional practice in the literacy cycle; There is a need to put in place mechanisms that favor awareness of the importance of protagonism in moments of continuing formation; the formative experiences permeated by the exchange of experience, as well as the playful experience favors the relationship between theory and practice, both in the children's learning process and in the process of re-signification of knowledge by teachers, it is necessary that the reflection on the practice and the practice is incorporated into the school routine, considering the time needed for the reflections to mature; and finally, it is evident that the National Pact Program for Literacy at the Right Age in Rio Grande do Sul was based on dialogue and participation, fundamental elements in a democratic context, thus collaborating with literacy practices in the public network. from Rio Grande do Sul.